Analisis Kualitas Pelayanan Instalasi Gawat Darurat (IGD) dan Rawat Inap (Kelas III) di Rumah Sakit Umum Daerah (RSUD) Dr. Tengku Mansyur Kota Tanjungbalai - Mahyaruddin Salim B; Isnaini Isnaini; Adam Adam (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This research is motivated by the quality of public services that have not been implemented properly, causing poor public service delivery which is a necessity for the government to make improvements in public services, one of which is the number of facilities that must be renovated and the lack of human resources at the Regional General Hospital (RSUD). Dr. Tengku Mansyur Tanjung City Hall. The purpose of this study is to determine the quality of services for the Emergency Room (IGD) and Inpatient Care (Class III) at the Regional General Hospital (RSUD) Dr. Tengku Mansyur Tanjungbalai City and to find out what factors are inhibiting the Emergency Installation (IGD) and Inpatient (Class III) Services at the Regional General Hospital (RSUD) Dr. Tengku Mansyur Tanjungbalai City. The research method uses a qualitative approach with a descriptive type. The results of this study indicate that based on PERMENPAN No. 19 of 2021 has gone well, this is because the five points in PERMENPAN such as types of services, service procedures, turnaround times, service fees and facilities and infrastructure have gone well. Then not only that there are inhibiting factors such as the need for additional human resources (HR) and improvement of hospital facilities that have not been maximized at the Regional General Hospital (RSUD) Dr. Tengku Mansyur Tanjungbalai City.